Mathematical Modelling and Simulation of Voltage Source Converter - B., Dhivya Haarinie; E., Latha Mercy (Journal of Electrical Engineering and Automation, 2025)
This research provides the mathematical modeling and simulation of a Voltage Source Converter (VSC) employed in advanced power systems for effective DC to AC voltage conversion. The research investigates the dynamics of VSCs, emphasizing important components like Pulse Width Modulation (PWM), dq current control, and PI controllers, coupled with an LCL filter for harmonic suppression. The control strategies, voltage and current regulation are proven using simulation responses with stable and precise output voltage and current. The results confirm the significance of robust control algorithms in obtaining optimum system performance and lay a groundwork for further study.